Assessment of Awareness and Approach Towards Hypertension Management Among General Practitioners (Academia Journal of Medicine, 2020)
Background: Hypertension and its complications are a global concern, due to its high prevalence especially as it often remains undiagnosed. The present study was conducted to assess awareness and approach towards hypertension management among general practitioners. Subjects & Methods: 150 general practitioners were questioned regarding the technique of measurement of blood pressure, diagnosis of prehypertension and hypertension, evaluations of newly diagnosed hypertensive patients, level of blood pressure to start pharmacological treatment and selection of antihypertensive agents in different clinical conditions. Results: Out of 150 subjects, males were 80 and females were 70. Cuff placement covering 2/3 of the arm at heart level was recommended by 84%, preferred position of patient was sitting replied by 52%, supine by 32% and standing and supine by 16%. The number of readings of blood pressure was 1 by 2%, 2 by 40% and 3 by 58%. Investigation preferred by GP was ECG by 91%, urine examination by 68%, serum creatinine by 82%, lipid profile by 80%, ultrasound of abdomen by 35%, serum potassium level by 72% and RBS by 98%. Common symptoms reported were morning headache by 70%, dizziness by 45%, palpitation by 52%, easy fatigability by 57% and impotence by 48%. The difference was significant (P< 0.05). Conclusion: Most of the GPs are well aware and updated about the initial lab investigations, symptoms and techniques.
Keywords: Awareness; Blood pressure; Hypertension